Micropropagation of Tetramolopium klossii (Moore) Mattfeld, endemic subalpine and alpine plant species to New Guinea - Ermayanti, Tri Muji; Hafiizh, Erwin Al; Martin, Andri Fadillah; Mandessy, Ary; Hermono, Arief; Mukhsia, Andi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2011)
The protocol of micropropagation of Tetramolopium klossii (Moore) Mattfeld through adventitious shoot proliferation was established. This is the first report of T. klossii tissue culture. Seeds were surface-sterilized by dipping them in 10% of ethanol for 1 min followed by soaking in 1% of sodium hypochlorite for 10 min. The sterile seeds were germinated on MS medium solidified with 8 g/l of agar, supplemented with 20 g/l of sucrose. Two-month old seedlings formed some shoot clumps on MS solid medium without addition of any plant growth regulators. Small clumps containing 4-6 adventitious shoots were used for shoot proliferation on MS solid medium containing 0; 0.1; 0.5; 1.0 and 2.0 mg/L of BAP (benzylaminopurine) or kinetin. The results showed that medium MS without cytokinins (control treatment), and the addition of 0.1 or 0.5 mg/L of BAP was more effective for shoot proliferation compared to the medium with addition of BAP at higher concentration and the addition of kinetin. In further subcultures, multiple shoots grown on MS medium without cytokinins was more vigorous than that of shoots grown on other media, so that the shoots were ready for rooting. Medium containing 0.5 mg/L of BAP was the best for maintaining multiple shoot formation. Shoots formed roots on MS medium containing half strength of macro nutrients. Keywords: Tetramolopium klossii, micropropagation, Murashige and Skoog medium, shoot multiplication